Cerebellar Hematoma Location: Implications for the Underlying Microangiopathy. Issue 1 (January 2018) - Pasi, Marco; Marini, Sandro; Morotti, Andrea; Boulouis, Gregoire; Xiong, Li; Charidimou, Andreas; Ayres, Alison M.; Lee, Myung Joo; Biffi, Alessandro; Goldstein, Joshua N.; Rosand, Jonathan; Gurol, M. Edip; et al.
Abstract : Background and Purpose—: Spontaneous cerebellar intracerebral hemorrhage (ICH) has been reported to be mainly associated with vascular changes secondary to hypertension. However, a subgroup of cerebellar ICH seems related to vascular amyloid deposition (cerebral amyloid angiopathy). We sought to determine whether location of hematoma in the cerebellum (deep and superficial regions) was suggestive of a particular hemorrhage-prone small-vessel disease pathology (cerebral amyloid angiopathy or hypertensive vasculopathy). Methods—: Consecutive patients with cerebellar ICH from a single tertiary care medical center were recruited. Based on data from pathological reports, patients were divided according to the location of the primary cerebellar hematoma (deep versus superficial). Location of cerebral microbleeds (CMBs; strictly lobar, strictly deep, and mixed CMB) was evaluated on magnetic resonance imaging. Results—: One-hundred and eight patients (84%) had a deep cerebellar hematoma, and 20 (16%) a superficial cerebellar hematoma. Hypertension was more prevalent in deep than in patients with superficial cerebellar ICH (89% versus 65%, respectively; P <0.05). Among patients who underwent magnetic resonance imaging, those with superficial cerebellar ICH had higher prevalence of strictly lobar CMB (43%) and lower prevalence of strictly deep or mixed CMB (0%) compared with those with deep superficial cerebellar ICH (6%, 17%, and 38%, respectively). In a multivariable model, presence of strictly lobar CMB was associated with superficial cerebellar ICH (odds ratio, 3.8; 95% confidence interval, 1.5–8.5; P =0.004). Conclusions—: Our study showed that superficial cerebellar ICH is related to the presence of strictly lobar CMB—a pathologically proven marker of cerebral amyloid angiopathy. Cerebellar hematoma location may thus help to identify those patients likely to have cerebral amyloid angiopathy pathology. Abstract : Supplemental Digital Content is available in the text.